Study of space plasma waves with flow. Issue 1 (1st February 2022) - Smith, T.; Strong, K.; Ibenki, S.; Sen, S.
Abstract : A fundamental reality throughout the space is the existence of magnetic field-aligned flows. Ion beams parallel to the magnetic field are a hallmark of the upward current region. Large electric fields found in the Earth's auroral zone produce shears in the ion flow both parallel and perpendicular to the magnetic field. These shears are observed simultaneously and result from the localized nature of the large, high-altitude, perpendicular electric fields and their equipotential closure at altitudes above the ionosphere. In regions where auroral ion beams form (3000–6000 km), the magnitude of the shear in the ion flow along the magnetic field is typically an order of magnitude larger than its magnitude in the perpendicular flow. At higher altitudes, shears in the parallel flow decrease with the magnetic field; while shears in the perpendicular flow are relatively constant with altitude. We study these interesting space plasma using a project which is meant mainly for students.